Combination of ovarian tissue harvesting and immature oocyte collection for fertility preservation increases preservation yield. Issue 4 (October 2015) - Hourvitz, A.; Yerushalmi, G.M.; Maman, E.; Raanani, H.; Elizur, S.; Brengauz, M.; Orvieto, R.; Dor, J.; Meirow, D.
Abstract The aim of this study was to evaluate the safety and efficacy of combined ovarian tissue cryopreservation and oocyte aspiration just before ovarian tissue cryobanking. A retrospective cohort study of fertility preservation patients treated in 2007–2013 in one tertiary centre was performed. A total of 255 cancer patients were admitted for fertility preservation: 142 patients underwent ovarian tissue cryopreservation only (OTC), 56 underwent OTC plus oocyte retrieval from ovarian tissue (OTIVM), nine underwent oocyte aspiration and in-vitro maturation (AIVM) and 48 underwent all three procedures. The total number of oocytes, total number of metaphase II (MII) oocytes, maturation rate, fertilization rate and total number of cryopreserved oocytes between groups were compared. The study found significantly more oocytes (P < 0.001), more MII oocytes (P < 0.001), better maturation rate (P < 0.01) and more cryopreserved oocytes (P < 0.05) with all three compared with OTIVM or OTC. No adverse outcome was observed by performing oocyte retrieval before ovarian resection for cryopreservation. In conclusion, oocyte aspiration just before ovarian tissue cryobanking is safe and gains more oocytes with a better maturation rate than ovarian tissue oocyte cryobanking alone. Better results were obtained with 3 days of stimulation before oocyte retrieval.